Development Oof Audio-Visual Learning Media to Increase the Ability of Makeup Skill Demonstration (Journal of Vocational and Career Education, 2022)
The purpose of this study is to develop audio-visual learning media to increase the ability to demonstrate fantasy makeup skills and analyze the feasibility, practicality, and effectiveness of audio-visual media for fantasy makeup courses in the Beauty Education Study Program at Universitas Negeri Semarang. This study applied the Research and Development method with the ADDIE model, which consists of five stages, namely analysis, design, development, implementation, and evaluation. The research subjects were 5th semester students of the cosmetology education study program totaling 30 students. The analysis of this research is audio visual media of wound character makeup. The instruments used by researchers were interview guidelines, media practicality questionnaires and questionnaires to measure the level of media feasibility. In order to test the validity, content validity test through expert opinion and questionnaire reliability using the KR20 formula were used. Data collection used one group pre-test post-test design which was then analyzed for normality and homogeneity tests. Based on the feasibility test, practicality test, and effectiveness test of audio-visual media to improve the ability to demonstrate fantasy makeup skills developed, according to the responses of media experts and material experts, the media is very feasible. Based on the responses of lecturers and students as user responses, the practicality of the media obtained very practical assessment criteria. From the effectiveness test in the experimental class, the media obtained quite effective and significant criteria to improve the ability to demonstrate fantasy makeup skills in the Beauty Education Study Program of Universitas Negeri Semarang.